Wide range in estimates of hydrogen emissions from infrastructure - Esquivel-Elizondo, Sofia; Hormaza Mejia, Alejandra; Sun, Tianyi; Shrestha, Eriko; Hamburg, Steven P.; Ocko, Ilissa B. (Frontiers in Energy Research, 2023)
Hydrogen holds tremendous potential to decarbonize many economic sectors, from chemical and material industries to energy storage and generation. However, hydrogen is a tiny, leak-prone molecule that can indirectly warm the climate. Thus, hydrogen emissions from its value chain (production, conversion, transportation/distribution, storage, and end-use) could considerably undermine the anticipated climate benefits of a hydrogen economy. Several studies have identified value chain components that may intentionally and/or unintentionally emit hydrogen.However, the amount of hydrogen emitted from infrastructure is unknown as emissions have not yet been empirically quantified. Without the capacity to make accurate direct measurements, over the past two decades, some studies have attempted to estimate total value chain and component-level hydrogen emissions using various approaches, e.g., assumptions, calculations via proxies, laboratory experiments, and theory-based models (simulations). Here, we synthesize these studies to provide an overview of the available knowledge on hydrogen emissions across value chains. Briefly, the largest ranges in estimated emissions rates are associated with liquefaction (0.15% to 10%), liquid hydrogen transporting and handling (2% to 20%), and liquid hydrogen refueling (2% to 15%). Moreover, present and future value chain emission rate estimates vary widely (0.2% to 20%). Field measurements of hydrogen emissions throughout the value chain are critically needed to sharpen our understanding of hydrogen emissions and, with them, accurately assess the climate impact of hydrogen deployment.